PENGARUH DEMONSTRASI TENTANG PERAWATAN PAYUDARA TERHADAP SIKAP IBU HAMIL PRIMIGRAVIDA DALAM PERAWATAN PAYUDARANYA - Yektiningsih, Erwin (Jurnal AKP, 2013)
Breast care is an act to treat breast milk to smooth spending and prevent the various problems of the breast.By this demonstration,it is expected to increase knowledge primigravida pregnant women about breast care, so it can change attitudes became more positive. But many primigravida pregnant women who haveÂ  less knowledge about breast care. The purpose of this study was knowing demonstration effect on breast careÂ  to the attitude of pregnant women in the treatment of breast primigravida in Connecticut Delima. The design we use in this study was pre-experimental with pre and post test approach. The population was 29 primigravida and the sample was taken by purposive sampling of 12 respondents. The instrument we use to know the attitude is using a checklist of 21 questions with check technique. By using Wilcoxon statistical test SPSS 11 For Windows. From this research, 75% pre demonstrations have a negative attitude and 25% have a positive attitude, the result of evaluation on post-demonstration of 100% have a positive attitude. ByWilcoxon statistical test , we found that the result (Ï = 0.002) <(Î± = 0.05).it means that Ho is refused and H1 is accepted .Â Â  So that, there is the Demonstration Effect on Breast Care of Pregnant Women Attitude primigravida in Nursing breasts in Connecticut Delima Mrs. Ami Gondang Village. From thisÂ  experiment, it is can be proven that someone will be able to change his attitude if they receive the influence from other people, such as nurses or midwives. With attitude positif in breast care is expected to avoid the problems of the breast. Â  Keywords: Demonstration, Breast Care, Attitudes, Primigravida.